"Social media perceptions of hip fractures: A two-year cross-sectional analysis". Issue 4 (April 2023) - Shaikh, Hashim JF; Brodell, BS James; Soin, Sandeep P
Abstract: Background: The outcomes of hip fracture rely heavily on subjective pain relief, and social media provides a remarkable lens to examine the patient experience. Methods: A search of public posts on Instagram and Twitter was performed over a 2 -year period, selected through use of the following hashtags: #hipfracture, #hipfracturerecovery, and #hipfracturerepair. A categorical classification system was used for media format (picture or video), perspective, timing, tone, and content. Post-popularity (number of likes) and geographic location were also recorded. Results: Of the Instagram posts analyzed, 50.6% were made by patients. The most common content included in Instagram posts was rehabilitation and or educational posts on hip fracture. Amongst the Twitter posts analyzed, 66% of posts were made by professional organizations. Frequently referenced themes included education, and posts produced by the hospital or surgeon. Of Facebook posts analyzed, 62.8% of posts were produced by businesses. Conclusion: Social media analysis is a powerful tool for evaluating characteristics important to patients. Instagram was used more by patients and focused on rehabilitation. Twitter posts were more frequently made by professional organizations and tended to be educational. Lastly, Facebook posts were made primarily by businesses and focused on marketing.